A mathematical model of control volume uncertainty for comparison calibration in water flow metrology. (December 2021) - Chun, Sejong
Abstract: Comparison calibration in water flow metrology requires control volume uncertainty because fluid properties within a pipeline are changing during flow measurement. However, an appropriate mathematical model has not been devised in a complete form to evaluate its measurement uncertainty according to the GUM. This study suggests an idea of combining the control volume uncertainty with thermal expansion as well as bulk modulus.